Sistem Rekomendasi Investasi Dengan Metode Weighted Product dengan Pembobotan ROC - Simamarta, Simon (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Investment is a crucial activity in long-term financial planning that requires careful consideration of various alternatives and criteria. Choosing the right investment is often challenging due to the diverse characteristics of each asset, such as return potential, risk, liquidity, and maintenance costs. To support the decision-making process, this study developed an investment recommendation system using the Weighted Product (WP) method with criterion weighting based on the Rank Order Centroid (ROC) approach. The WP method is applied to calculate the preference scores of each investment alternative, while ROC is used to determine objective criterion weights based on their ranked importance. The study evaluated ten investment alternatives using six evaluation criteria. The results indicate that Gold Bullion is the most recommended investment, achieving the highest WP score (1.0364), followed by Property (0.9620) and Luxury Jewelry and Watches (0.8558). The proposed system proves to be effective in producing rational and consistent recommendations that support data-driven decision-making. This research contributes to the development of adaptive and objective investment decision support systems.